2013
DOI: 10.1177/0333102413515336
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of telephone-based motivational interviewing for adolescent chronic headache with medication overuse

Abstract: Our findings provided some preliminary, albeit limited, support for MI as an approach to improve outcomes for adolescent medication-overuse headache (MOH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…After screening for title and abstract we performed full text screening of 21 publications of which 18 were regarded eligible presenting 16 trials (see figure 1). Three publications were excluded because of no RCT [10], including only children [33] and not including MOH patients [31]. …”
Section: Search Resultsmentioning
confidence: 99%
“…After screening for title and abstract we performed full text screening of 21 publications of which 18 were regarded eligible presenting 16 trials (see figure 1). Three publications were excluded because of no RCT [10], including only children [33] and not including MOH patients [31]. …”
Section: Search Resultsmentioning
confidence: 99%
“…15 Also, prior research demonstrated that the addition of individual MI pre-treatment (one in-person and three telephone-based sessions) to group CBT for a heterogeneous group of anxiety disorders led to significantly better outcomes than for CBT without MI. 15 Also, prior research demonstrated that the addition of individual MI pre-treatment (one in-person and three telephone-based sessions) to group CBT for a heterogeneous group of anxiety disorders led to significantly better outcomes than for CBT without MI.…”
Section: Discussionmentioning
confidence: 99%
“…13 One study found that a brief telephone intervention for as little as 15 minutes on two occasions was effective in motivating participants to attend psychotherapy after MI. 15 We sought to examine brief, non-clinician delivered, telephone-based MI and its effect compared to treatment as usual (TAU) on rates of initiating, scheduling, and attending a first behavioral therapy session after specialist referral for behavioral therapy for migraine. 15 We sought to examine brief, non-clinician delivered, telephone-based MI and its effect compared to treatment as usual (TAU) on rates of initiating, scheduling, and attending a first behavioral therapy session after specialist referral for behavioral therapy for migraine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…118 Brief targeted educational and motivation enhancement strategies alone, such as nurse education or between-visit motivational phone calls, have also demonstrated some efficacy to modify specific acute medication adherence behaviors (e.g., taking medication early, or reducing medication overuse). 113,119 Several steps can be taken to increase medication adherence in patients with headaches. 118 Specifically, assessing how individuals with headache take their medications can provide valuable information for the clinical assessment, and allow for targeted interventions.…”
Section: Medication Adherencementioning
confidence: 99%